Логистика обслуживания материальных потоков в системе товарных рынков - Тараканов, Н.Л. (Економічні інновації, 2013)
В структуре сбытовой логистики обоснована целесообразность учета типов товарных рынков, на которых реализуется продукция. Выполнена типология рынков, в основу которой положен критерий логистических условий сбыта продукции. Сформулировано понятие базового звена логистического канала, обоснован набор требований относительно доступа к пользованию логистическими услугами, их специализации, учета внешней рыночной среды. The tendencies of development of logistic chains of material flow service are investigated. In the scope of market logistics there is reasoned the expedience of accounting of types of commodity markets, in which goods are realized. The typology of markets on the basis of dependence criterion of logistic characteristics of the markets on goods marketing conditions. The notion of basic link of logistic channel is formulated, and its functions are exposed.